Innovation and Technology: Determining Factors of Handphone Sales in Sikapaiya - Antika, Rindi; Erwin, Erwin; Mas'ud, Anis Anshari (Universitas Negeri Gorontalo, 2025)
Purpose: This study investigates the impact of innovation and technological progress on smartphone sales in Sikapaiya, Majene.Design/Methodology/Approach: This study uses a descriptive quantitative approach with multiple linear regression analysis via SPSS 25 on 100 respondents.Findings: The results show that innovation and technological progress have a significant effect on smartphone sales, both partially and simultaneously. The findings have significant implications for increasing smartphone sales, suggesting that mobile phone companies can boost sales by developing better innovations and technologies.